The Limitless Zawiya and the Infinite Library. Rethinking the Epistemology of Contemporary Sufism and Digital Islamic Thought - Antonio de Diego González (Antípoda: Revista de Antropología y Arqueología)
Contemporary Sufism has not been untouched by the digital revolution. Tradition and modernity intersect in the spiritual and esoteric practices of thousands of Muslims in an increasingly globalized world. This convergence has significantly transformed the epistemological and social foundations of these practices and those who engage in them. This paper examines the digital revolution’s impact on one of the most popular branches of globalized Sufism, the tariqa Tijaniyya, from 2000 to 2020, exploring how it has shaped doctrinal, social, and spiritual discourse in contemporary Sufism. The primary goal is to analyze the epistemological dynamics of digital Sufism in relation to traditional models and to assess how these changes influence its spiritual and intellectual practices. This study will employ an interdisciplinary methodology that combines physical and digital collaborative ethnography, symbolic hermeneutics, and philosophy of religion. The ontological turn in anthropology is a key consideration in the ethnographies presented in these texts and their subsequent analysis. The paper concludes that the tariqa Tijaniyya has not been isolated from the profound social transformations of the digital age. In response, it has adapted and redefined its traditional epistemic categories, presenting new challenges for senior scholars of the tariqa. Two emerging concepts—the limitless zawiya and the infinite library—represent the latest challenges to this traditional and esoteric practice, awaiting further exploration. The originality of this research lies in its potential to serve as a foundation for studies in other Islamic contexts, as well as for other religious or intellectual expressions with epistemic models grounded in the primacy of ritual, esotericism, and tradition